Evidence linking exposure of fish primary macrophages to antibiotics activates the NF-kB pathway. (May 2020) - Qiu, Wenhui; Hu, Jiaqi; Magnuson, Jason T.; Greer, Justin; Yang, Ming; Chen, Qiqing; Fang, Meijuan; Zheng, Chunmiao; Schlenk, Daniel
Graphical abstract: Highlights: A KEGG analysis in common DEGs of the antibiotics showed the activation of NF-κB. Low levels of antibiotics induced a NF-κB-mediated immune response. Induction of cytokines by antibiotics were minor when compared to LPS treatment. Exposure of fish macrophages to low doses of antibiotics activates the NF-kB pathway. Abstract: Low doses of antibiotics are ubiquitous in the marine environment and may exert negative effects on non-target aquatic organisms. Using primary macrophages of common carp, we investigated the mechanisms of action following exposure to several common antibiotics; cefotaxime, enrofloxacin, tetracycline, sulfamonomethoxine, and their mixtures, and explored the immunomodulatory effects associated with the nuclear factor-κB (NF-κB) signaling pathway. A KEGG pathway analysis was conducted using the sixty-six differentially expressed genes found in all treatments, and showed that exposure to 100 μg/L of antibiotics could affect regulation of the NF-κB signaling pathway, suggesting that activation of NF-κB is a common response in all four classes of antibiotics. In addition, the four antibiotics induced nf-κb and NF-κB-associated cytokines expression, as verified by qPCR, however, these induction responses by four antibiotics were minor when compared to the same concentration of LPS treatment (100 μg/L). Antagonists of NF-κB blocked many of the immune effects of the antibiotics, providing evidence that NF-κB pathways mediate the actions of all four antibiotics. Moreover, exposure to environmentally relevant, low levels (0.01–100 μg/L) of antibiotics induced a NF-κB-mediated immune response, including endogenous generation of ROS, activity of antioxidant enzymes, as well as expression of cytokine and apoptosis. Moreover, exposure to mixtures of antibiotics presented greater effects on most tested immunological parameters than exposure to a single antibiotic, suggesting additive effects from multiple antibiotics in the environment. This study demonstrates that exposure of fish primary macrophages to low doses of antibiotics activates the NF-kB pathway.